2007
DOI: 10.1111/j.1475-2743.2006.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaching and crop uptake of N, P and K from organic and conventional cropping systems on a clay soil

Abstract: In this study, three types of cropping systems with different nutrient management strategies were studied on a clay soil with the aim of comparing leaching of N, P and K and obtaining knowledge on nutrient budgets. A conventional cropping system with cereals and application of mineral fertilizers (CON) was compared with two organic cropping systems, one without animal manure in which green manure crops were used for N supply (OGM) and one where animal manure (cattle slurry) was applied (OAM). Leaching and crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 24 publications
4
53
0
Order By: Relevance
“…Leifert et al, 2007;Eyre et al, 2009), where comparisons were made not only between organic and conventional systems, but between all combinations of organic vs. conventional plant protection, nutrient management and rotations optimized for organic or conventional production, in order to investigate which of these factors are primarily responsible for differences in productivity, environmental effects or product quality. Other studies of organic cereal rotations have focused on the use of animal vs. green manures (Torstensson et al, 2006;Aronsson et al, 2007;Doltra et al, 2011). However, though these experiments were very different in their approach, they were all aimed to investigate methods that were already in common use in organic production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leifert et al, 2007;Eyre et al, 2009), where comparisons were made not only between organic and conventional systems, but between all combinations of organic vs. conventional plant protection, nutrient management and rotations optimized for organic or conventional production, in order to investigate which of these factors are primarily responsible for differences in productivity, environmental effects or product quality. Other studies of organic cereal rotations have focused on the use of animal vs. green manures (Torstensson et al, 2006;Aronsson et al, 2007;Doltra et al, 2011). However, though these experiments were very different in their approach, they were all aimed to investigate methods that were already in common use in organic production.…”
Section: Introductionmentioning
confidence: 99%
“…Birkhofer et al, 2008;Aronsson et al, 2007) or produce higher quality food than conventional methods (e.g. Dangour et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This was also shown in a study carried out on a clay soil in southwest Sweden, in which conventional and organic systems were compared (Aronsson et al, 2007). It is also obvious from these studies that N leaching per hectare is not reduced when organic manures are used instead of inorganic N fertilisers.…”
Section: Are There Any Water Quality Benefits Associated With Organicmentioning
confidence: 59%
“…Irrespective of the organic N source used in organic crop production, several studies have shown that they provide the crop with less N than similar amounts of N applied as mineral fertiliser (e.g. Thomsen et al, 1997;Aronsson et al, 2007;Bergström and Kirchmann, 2006). Thus, a lower N use efficiency seems to be a common problem in organic cropping systems, despite the fact that N inputs tend to be lower in organic systems than in conventional.…”
Section: Nutrient-use Efficiency In Organic Andf Conventional Croppinmentioning
confidence: 99%
See 1 more Smart Citation